2009
DOI: 10.1002/eji.200839129
|View full text |Cite
|
Sign up to set email alerts
|

Clonal dissection of the human memory B‐cell repertoire following infection and vaccination

Abstract: Summary The analysis of the human memory B cell repertoire is of both fundamental and practical significance. We developed a simple method for the selective activation of memory B cells in total fresh or frozen PBMC using a combination of R848 and IL-2. In these conditions 30–40% of memory B cells generated clones producing on average 200 ng IgG in 10 days. This method was used to measure the frequency of antigen specific memory B cells as well as the fine specificity, crossreactivity and neutralizing activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
184
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 43 publications
8
184
0
Order By: Relevance
“…The maximum of TT-specific PC and memory B cell numbers were observed on day 7 and day 14, respectively, after secondary immunization. This is in concordance with previous studies monitoring immune responses after TT (7,19) or influenza immunization (20,21). In these studies, peaks of Ag-specific PCs and memory B cells could be observed on days 6-8 and 14-28, respectively.…”
Section: Kineticssupporting
confidence: 92%
“…The maximum of TT-specific PC and memory B cell numbers were observed on day 7 and day 14, respectively, after secondary immunization. This is in concordance with previous studies monitoring immune responses after TT (7,19) or influenza immunization (20,21). In these studies, peaks of Ag-specific PCs and memory B cells could be observed on days 6-8 and 14-28, respectively.…”
Section: Kineticssupporting
confidence: 92%
“…The response to CpG was not as pronounced, whether in the presence or absence of IL-2. The nonproliferating cells in these cultures were most probably the naive B cells [31]. Including anti-Ig showed that this, together with R848 and IL-2, induced the highest level of proliferation.…”
Section: The Cd21 -/Low B Cells Lack Expression Of the Abcb1 Transportermentioning
confidence: 83%
“…Nevertheless, these responses to benign microbes are mainly focused on the intestinal mucosa, unless the intestinal permeability barrier is breached and the live organism reaches systemic secondary lymphoid structures (Macpherson et al 2000;Konrad et al 2006). Weak systemic responses may be enough to induce polyclonal expansions (Zeng et al 2016), making pre-induced vaccine responses more durable (Pinna et al 2009), but are likely less ideal for de novo induction of systemic protective immunity unless one were to compromise by making the organism more invasive.…”
Section: Agitation Across Federal Borders: the Points Test For Differmentioning
confidence: 99%